2021
DOI: 10.1108/rsr-04-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Reading Format International Study (ARFIS): final results of a comparative survey analysis of 21,265 students in 33 countries

Abstract: PurposeThis paper presents the complete findings from the Academic Reading Format International Study (ARFIS), the world's largest study of tertiary students' format preferences and behaviors. The analysis of ARFIS proceeded in two stages. This paper reveals results from the second stage for the first time and compares them with the earlier results. The authors then present and discuss the results from the combined datasets of 21,266 students in 33 countries.Design/methodology/approachA total of 44 members in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
4
9
0
Order By: Relevance
“…Majorities in all countries also agreed or strongly agreed that they could focus better and remember the information better when they read in print. Final quantitative analysis of all 21,265 students in 33 countries ( Mizrachi et al, 2021 ) confirmed earlier findings. ARFIS researchers then performed a qualitative analysis of English language comments by students categorized as either print preferrers or electronic preferrers to discover the reasons for their preferences, and under what circumstances they would consider reading a text in their less preferred format ( Mizrachi & Salaz, 2020 ).…”
Section: Literature Reviewsupporting
confidence: 80%
See 3 more Smart Citations
“…Majorities in all countries also agreed or strongly agreed that they could focus better and remember the information better when they read in print. Final quantitative analysis of all 21,265 students in 33 countries ( Mizrachi et al, 2021 ) confirmed earlier findings. ARFIS researchers then performed a qualitative analysis of English language comments by students categorized as either print preferrers or electronic preferrers to discover the reasons for their preferences, and under what circumstances they would consider reading a text in their less preferred format ( Mizrachi & Salaz, 2020 ).…”
Section: Literature Reviewsupporting
confidence: 80%
“…To the surprise of many in various areas of education, studies continued to show that tertiary students preferred to read their academic texts in print for deep learning tasks such as when they needed to focus and internalize the information ( Dilevko & Gottlieb, 2002 ; Liu, 2006 ; Mizrachi, 2015 ; Mizrachi & Salaz, 2020 ). One of the largest studies to date documenting this phenomenon is the Academic Reading Format International Study (ARFIS) ( Mizrachi et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of these advantages, many institutions of higher education have adopted e-texts by integrating them directly into learning management systems to provide students with new and diversified learning opportunities and first-day access to materials (Chapman et al, 2016;Dennis, 2011). Despite the growing availability of e-texts and the multitude of available learning tools, the acceptance of e-texts is slower than was predicted in K-12 and post-secondary settings (Mizrachi et al, 2021). According to the world's largest study of reading format preferences and behaviours in tertiary students (Mizrachi at el., 2021), majorities of students from 33 countries prefer print over e-text for academic readings.…”
Section: Integration Of E-textbooks In K-12 and Higher Educationmentioning
confidence: 99%